Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To verify the equation [tex]\( a \times (b - c) = (a \times b) - (a \times c) \)[/tex] given [tex]\( a = \frac{-6}{7} \)[/tex], [tex]\( b = \frac{1}{3} \)[/tex], and [tex]\( c = \frac{-4}{15} \)[/tex], let's go through the mathematical steps in detail.
### Step 1: Calculate [tex]\( b - c \)[/tex]
First, we need to find the difference [tex]\( b - c \)[/tex].
[tex]\[ b - c = \frac{1}{3} - \frac{-4}{15} \][/tex]
To subtract these two fractions, we need a common denominator. The least common multiple of 3 and 15 is 15. Convert both fractions to have this common denominator:
[tex]\[ \frac{1}{3} = \frac{5}{15} \][/tex]
[tex]\[ \frac{-4}{15} = \frac{-4}{15} \][/tex]
Now we can subtract the fractions:
[tex]\[ b - c = \frac{5}{15} - \frac{-4}{15} = \frac{5}{15} + \frac{4}{15} = \frac{9}{15} = 0.6 \][/tex]
### Step 2: Calculate [tex]\( a \times (b - c) \)[/tex]
Next, we need to multiply [tex]\( a \)[/tex] by the result from the previous step:
[tex]\[ a \times (b - c) = \frac{-6}{7} \times 0.6 \][/tex]
We convert 0.6 to a fraction:
[tex]\[ 0.6 = \frac{6}{10} = \frac{3}{5} \][/tex]
So,
[tex]\[ a \times (b - c) = \frac{-6}{7} \times \frac{3}{5} = \frac{-18}{35} \approx -0.5142857142857142 \][/tex]
### Step 3: Calculate [tex]\( a \times b \)[/tex]
Now we calculate [tex]\( a \times b \)[/tex]:
[tex]\[ a \times b = \frac{-6}{7} \times \frac{1}{3} \][/tex]
[tex]\[ a \times b = \frac{-6}{21} = \frac{-2}{7} \approx -0.2857142857142857 \][/tex]
### Step 4: Calculate [tex]\( a \times c \)[/tex]
Next, we calculate [tex]\( a \times c \)[/tex]:
[tex]\[ a \times c = \frac{-6}{7} \times \frac{-4}{15} \][/tex]
[tex]\[ a \times c = \frac{24}{105} = \frac{8}{35} \approx 0.22857142857142856 \][/tex]
### Step 5: Calculate [tex]\( (a \times b) - (a \times c) \)[/tex]
Now we need to find the difference between [tex]\( a \times b \)[/tex] and [tex]\( a \times c \)[/tex]:
[tex]\[ (a \times b) - (a \times c) = \frac{-2}{7} - \frac{8}{35} \][/tex]
First, convert [tex]\(\frac{-2}{7}\)[/tex] to have a common denominator with [tex]\(\frac{8}{35}\)[/tex]:
[tex]\[ \frac{-2}{7} = \frac{-10}{35} \][/tex]
Now subtract the fractions:
[tex]\[ (a \times b) - (a \times c) = \frac{-10}{35} - \frac{8}{35} = \frac{-18}{35} \approx -0.5142857142857142 \][/tex]
### Step 6: Verification
At this point, we compare the results from Step 2 and Step 5:
[tex]\[ a \times (b - c) \approx -0.5142857142857142 \][/tex]
[tex]\[ (a \times b) - (a \times c) \approx -0.5142857142857142 \][/tex]
Since both results are approximately equal, we have verified that:
[tex]\[ a \times (b - c) = (a \times b) - (a \times c) \][/tex]
Thus, the equation holds true.
### Step 1: Calculate [tex]\( b - c \)[/tex]
First, we need to find the difference [tex]\( b - c \)[/tex].
[tex]\[ b - c = \frac{1}{3} - \frac{-4}{15} \][/tex]
To subtract these two fractions, we need a common denominator. The least common multiple of 3 and 15 is 15. Convert both fractions to have this common denominator:
[tex]\[ \frac{1}{3} = \frac{5}{15} \][/tex]
[tex]\[ \frac{-4}{15} = \frac{-4}{15} \][/tex]
Now we can subtract the fractions:
[tex]\[ b - c = \frac{5}{15} - \frac{-4}{15} = \frac{5}{15} + \frac{4}{15} = \frac{9}{15} = 0.6 \][/tex]
### Step 2: Calculate [tex]\( a \times (b - c) \)[/tex]
Next, we need to multiply [tex]\( a \)[/tex] by the result from the previous step:
[tex]\[ a \times (b - c) = \frac{-6}{7} \times 0.6 \][/tex]
We convert 0.6 to a fraction:
[tex]\[ 0.6 = \frac{6}{10} = \frac{3}{5} \][/tex]
So,
[tex]\[ a \times (b - c) = \frac{-6}{7} \times \frac{3}{5} = \frac{-18}{35} \approx -0.5142857142857142 \][/tex]
### Step 3: Calculate [tex]\( a \times b \)[/tex]
Now we calculate [tex]\( a \times b \)[/tex]:
[tex]\[ a \times b = \frac{-6}{7} \times \frac{1}{3} \][/tex]
[tex]\[ a \times b = \frac{-6}{21} = \frac{-2}{7} \approx -0.2857142857142857 \][/tex]
### Step 4: Calculate [tex]\( a \times c \)[/tex]
Next, we calculate [tex]\( a \times c \)[/tex]:
[tex]\[ a \times c = \frac{-6}{7} \times \frac{-4}{15} \][/tex]
[tex]\[ a \times c = \frac{24}{105} = \frac{8}{35} \approx 0.22857142857142856 \][/tex]
### Step 5: Calculate [tex]\( (a \times b) - (a \times c) \)[/tex]
Now we need to find the difference between [tex]\( a \times b \)[/tex] and [tex]\( a \times c \)[/tex]:
[tex]\[ (a \times b) - (a \times c) = \frac{-2}{7} - \frac{8}{35} \][/tex]
First, convert [tex]\(\frac{-2}{7}\)[/tex] to have a common denominator with [tex]\(\frac{8}{35}\)[/tex]:
[tex]\[ \frac{-2}{7} = \frac{-10}{35} \][/tex]
Now subtract the fractions:
[tex]\[ (a \times b) - (a \times c) = \frac{-10}{35} - \frac{8}{35} = \frac{-18}{35} \approx -0.5142857142857142 \][/tex]
### Step 6: Verification
At this point, we compare the results from Step 2 and Step 5:
[tex]\[ a \times (b - c) \approx -0.5142857142857142 \][/tex]
[tex]\[ (a \times b) - (a \times c) \approx -0.5142857142857142 \][/tex]
Since both results are approximately equal, we have verified that:
[tex]\[ a \times (b - c) = (a \times b) - (a \times c) \][/tex]
Thus, the equation holds true.
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.